Effect of Sodium Lauryl Sulphate on the Solubility and Viscosity Properties of Cassava Starch - REVAMMA, R. (Asian Journal of Chemistry, 2010)
Surfactants and lipids are known to modify the swelling and rheological properties of starches. The action is due to complexation of the amylose fraction of the starch with the surfactant. The effect of 9 different concentrations of sodium lauryl sulphate (SLS) on the swelling, solubility and viscosity properties of cassava starch was studied. The peaks in swelling volume were found to be between 0.005 and 0.1 % of the surfactant. No breakdown effect was observed even when the complex was subjected to steam pressure treatments of 5, 10 and 15 psi, showing the stability of the complex. The solubility of starch was found to be influenced by different factors like concentration of surfactant, concentration of starch and temperature. The peak viscosity of starch remained almost same upto 0.05 % surfactant and then showed a noticeable increase upto 0.5 % and then declined to the control value. A second peak was observed during cooling.